La piétonisation des centres : un nouveau rapport à la proximité dans les villes moyennes ? - Emilie Roudier (GéoProximitéS)
The Action Cœur de Ville program, launched by the French government in 2018, encourages projects in favor of walking in the centers of mid-sized cities. This article proposes to focus on the numerous pedestrianization projects of the winning local cities and the challenges of reducing the role of the automobile. It reflects a circulation of development models and mobility policies between mid-sized cities on the one hand, and between metropolises and mid-sized cities on the other hand.